Pregnancy and β-thalassemia: an Italian multicenter experience - Origa, R.; Piga, A.; Quarta, G.; Forni, G. L.; Longo, F.; Melpignano, A.; Galanello, R. (Haematologica (Roma), 2010)
Recent advances in the management of thalassemia have significantly improved life expectancy and quality of life of patients with this hemoglobinopathy, with a consequent increase in their reproductive potential and desire to have children. We describe the methods of conception and delivery, as well as the course and outcome of pregnancy including transfusions, iron overload and chelation in 46 women with thalassemia major (58 pregnancies) and in 11 women with thalassemia intermedia (17 pregnancies). Conception was achieved after gonadotrophin-induced ovulation in 33 of the women with thalassemia major and spontaneously in all of those with thalassemia intermedia. Among the women with thalassemia major, 91% of the pregnancies resulted in successful delivery of 45 singleton live-born neonates, five sets of twins and one set of triplets. No secondary complications of iron overload developed or worsened during pregnancy. When considering only the singleton pregnancies, the proportion of babies with intrauterine growth retardation did not differ from that reported in the general Italian population. The high prevalence of pre-term births (32.7%) was mostly related to multiple pregnancies and precautionary reasons. Pregnancy was safe in most women with thalassemia major or intermedia. However, women with thalassemia intermedia who had never previously been transfused or who had received only minimal transfusion therapy were at risk of severe alloimmune anemia if blood transfusions were required during pregnancy. Provided that a multidisciplinary team is available, pregnancy is possible, safe and usually has a favorable outcome in patients with thalassemia. In women with hypogonadotropic hypogonadism, gonadal function is usually intact and fertility is usually retrievable.